2013
DOI: 10.1007/s00392-013-0607-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cells as predictors of secondary manifestations of cardiovascular disease: design of the CIRCULATING CELLS study

Abstract: Biomarkers for primary or secondary risk prediction of cardiovascular disease (CVD) are urgently needed to improve individual treatment and clinical trial design. The vast majority of biomarker discovery studies has concentrated on plasma/serum as an easily accessible source. Although numerous markers have been identified, their added predictive value on top of traditional risk factors has been limited, as the biological specimen does not specifically reflect expression profiles related with CVD progression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Taken together, our preliminary data suggest the potential relevance of circulating monocyte phenotype features in predicting CAD stage and progression, assessed by histology, in a swine model of experimentally induced ATS.In agreement with human clinical trials, demonstrating the importance of the circulating immune effector characterization in predicting cardiovascular disease outcome [43], our experimental findings, albeit preliminary, support a role of the circulating monocyte functional state in coronary plaque initiation and early progression, providing the basis for a better knowledge of immune cell contribution to CAD development in humans.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, our preliminary data suggest the potential relevance of circulating monocyte phenotype features in predicting CAD stage and progression, assessed by histology, in a swine model of experimentally induced ATS.In agreement with human clinical trials, demonstrating the importance of the circulating immune effector characterization in predicting cardiovascular disease outcome [43], our experimental findings, albeit preliminary, support a role of the circulating monocyte functional state in coronary plaque initiation and early progression, providing the basis for a better knowledge of immune cell contribution to CAD development in humans.…”
Section: Discussionsupporting
confidence: 83%
“…Recently, considerable focus has been placed on circulating cells, as circulating monocytes, involved in cardiovascular disease [23] and CaSR expression has been demonstrated in circulating monocytes [25,26]. We have previously shown that CaSR expression in circulating monocytes could represent an accessible biomarker to monitor an individual’s ‘CaSR status’ under nonpathological conditions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes/macrophages are known to play a crucial role in the pathogenesis of atherosclerosis and a considerable focus has been placed on their precursor, circulating monocytes as predictors of cardiovascular disease [2123]. Intriguingly, CaSR expression has been demonstrated in human circulating monocytes and extracellular calcium has been shown to be a chemokinetic agent for human circulating monocytes [2426].…”
Section: Introductionmentioning
confidence: 99%
“…When secondary to CAD, the biomarkers are usually found in very low concentrations compared with other more abundant proteins such as albumin or immunoglobulins. 41 Although platelets cannot be stored and batched, they are abundant in the circulation and reflect both prothrombotic potential and atherosclerotic plaque composition. Circulating platelets interact with the vessel wall and the atherosclerotic plaque incorporating pathogenic material (protein, cytoplasm, and messenger ribonucleic acid [mRNA]) from the atherosclerotic plaque.…”
Section: Platelets As Biomarkers Of Coronary Artery Diseasementioning
confidence: 99%